Systematic review of the therapeutic use of Schwann cells in the repair of peripheral nerve injuries: Advancements from animal studies to clinical trials - Vallejo, Frederic A.; Diaz, Anthony; Errante, Emily L.; Smartz, Taylor; Khan, Aisha; Silvera, Risset; Brooks, Adriana E.; Lee, Yee-Shuan; Burks, Stephen Shelby; Levi, Allan D. (Frontiers in Cellular Neuroscience, 2022)
Objective To systematically evaluate the literature on the therapeutic use of Schwann cells (SC) in the repair of peripheral nerve injuries. Methods The Cochrane Library and PubMed databases were searched using terms [(“peripheral nerve injury” AND “Schwann cell” AND “regeneration”) OR (“peripheral nerve injuries”)]. Studies published from 2008 to 2022 were eligible for inclusion in the present study. Only studies presenting data from in-vivo investigations utilizing SCs in the repair of peripheral nerve injuries qualified for review. Studies attempting repair of a gap of ≥10 mm were included. Lastly, studies needed to have some measure of quantifiable regenerative outcome data such as histomorphometry, immunohistochemical, electrophysiology, or other functional outcomes. Results A search of the PubMed and Cochrane databases revealed 328 studies. After screening using the abstracts and methods, 17 studies were found to meet our inclusion criteria. Good SC adherence and survival in conduit tubes across various studies was observed. Improvement in morphological and functional outcomes with the use of SCs in long gap peripheral nerve injuries was observed in nearly all studies. Conclusion Based on contemporary literature, SCs have demonstrated clear potential in the repair of peripheral nerve injury in animal studies. It has yet to be determined which nerve conduit or graft will prove superior for delivery and retention of SCs for nerve regeneration. Recent developments in isolation and culturing techniques will enable further translational utilization of SCs in future clinical trials.